Resolving transient temperature and density during ultrafast laser ablation of aluminum - Winter, Jan; Redka, David; Minár, Ján; Schmidt, Michael; Huber, Heinz P. (Applied Physics A: Materials Science and Processing, 2023)
To understand the dynamics of ultrashort-pulse laser ablation, the interpretation of ultrafast time-resolved optical experiments is of utmost importance. To this end, spatiotemporally resolved pump-probe ellipsometry may be utilized to examine the transiently changing dielectric function of a material, particularly when compared to two-temperature model simulations. In this work, we introduce a consistent description of electronic transport as well dielectric function for bulk aluminum, which enables unambiguous quantitative predictions of transient temperature and density variations close to the surface after laser excitation. Potential contributions of these temperature and density fluctuations to the proposed optical model are investigated. We infer that after the thermal equilibrium of electrons and lattice within a few picoseconds, the real part of the dielectric function mostly follows a density decrease, accompanied by an early mechanical motion due to stress confinement. In contrast, the imaginary part is susceptible to a complicated interaction between time-varying collision frequency, plasma frequency, and a density dependency of the interband transitions. The models proposed in this study permit an outstanding quantitative prediction of the ultrashort-pulse laser ablation’s final state and transient observables. Consequently, it is anticipated that in the future, these models will provide a quantitative understanding of the dynamics and behavior of laser ablation. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-09-15
Keywords: Complex refractive index; Density influence; Time-resolved ellipsometry; Transport and optical properties; Two-temperature model